Differential virome composition and richness between children's diarrheagenic stools kept at ultra-low temperatures for long-term - Adriana Becerra; Pavel Iša; Ana Lorena Gutiérrez-Escolano; Federico Raúl Velázquez; Javier Torres; Carlos Federico Arias; Teresa Estrada-Garcia (Journal of Infection in Developing Countries)
Introduction: Diarrhoeal illness is the second cause of morbidity/mortality among children from less-developed regions worldwide. Nonetheless, there is scarce information regarding their gut microbiome.